2017
DOI: 10.1371/journal.pone.0181739
|View full text |Cite
|
Sign up to set email alerts
|

Transition of the intestinal microbiota of cats with age

Abstract: The transition of intestinal microbiota with age has been well described in humans. However, the age-related changes in intestinal microbiota of cats have not been well studied. In the present study, we investigated the composition of intestinal microbiota of cats in 5 different age groups (pre-weanling, weanling, young, aged, senile) with a culture-based method. For lactobacilli and bifidobacteria, we also quantified with molecular-based method, real-time PCR. The results suggested that the composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 19 publications
0
32
2
3
Order By: Relevance
“…Although key bacterial members are commonly present in the faecal microbial community of healthy dogs and cats, a finding that is indicative of a core faecal microbiota, the taxonomic composition may be subject to changes and modulations due to the influence of several factors including diet (Bresciani et al ., 2018; Schmidt et al ., 2018; Alessandri et al ., 2019a–c), age (Fahey et al ., 2008; Masuoka et al ., 2017), metabolic disorders (i.e. diabetes or obesity; Alexander et al ., 2018; Salas‐Mani et al ., 2018), intestinal dysbiosis (diarrhoea or inflammatory bowel diseases) or cancer (Honneffer et al ., 2014; Omori et al ., 2017; Kalenyak et al ., 2018), as well as anthropogenic influences (Alessandri et al ., 2019a–c; Fig.…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although key bacterial members are commonly present in the faecal microbial community of healthy dogs and cats, a finding that is indicative of a core faecal microbiota, the taxonomic composition may be subject to changes and modulations due to the influence of several factors including diet (Bresciani et al ., 2018; Schmidt et al ., 2018; Alessandri et al ., 2019a–c), age (Fahey et al ., 2008; Masuoka et al ., 2017), metabolic disorders (i.e. diabetes or obesity; Alexander et al ., 2018; Salas‐Mani et al ., 2018), intestinal dysbiosis (diarrhoea or inflammatory bowel diseases) or cancer (Honneffer et al ., 2014; Omori et al ., 2017; Kalenyak et al ., 2018), as well as anthropogenic influences (Alessandri et al ., 2019a–c; Fig.…”
Section: Insights Into the Gut Microbiota Of Healthy Dogs And Catsmentioning
confidence: 99%
“…In a similar way, a culture‐based analysis revealed that Enterobacteriaceae and Enterococcus spp. dominated the gut microbiota of pre‐weanling kittens, while their abundance decreased throughout life (Masuoka et al ., 2017). In addition, as observed in dogs, also the gut microbiota of lactating kittens is characterized by high numbers of Clostridium spp.…”
Section: Evolution Of the Canine And Feline Intestinal Community Durimentioning
confidence: 99%
“…However, the role of pCS has not been explored in veterinary medicine. Various studies have evaluated the gastrointestinal microbiome of cats in health and in disease, but the fecal microbiome in cats with CKD and its association with IS and pCS have not been characterized. The primary aim of our study was to characterize the fecal microbiome of cats with CKD in comparison to healthy control cats.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, the development of microbial therapies with weight-loss applications in obese cats and dogs is challenging [7], in part due to the little we know about microbes and obesity [92,93] in these animal species and the wide inter-individual variation in the gut microbiome. This variation in the gut microbiome in pets is associated with the passing of time and aging [94][95][96][97][98], environmental factors, including diet [99], microbes in surrounding people [100], breed and other host genetics factors [101,102], clinical and subclinical conditions [91,93,103], gender [104], and behavior [105]. Here, we discuss the literature on feline and canine gut microbiota with regards to Verrucomicrobia-and Akkermansia-like 16S rRNA sequences (Table 1).…”
Section: The Feline and Canine Gut Microbiotamentioning
confidence: 99%